THE ENSURING ANTY-TERRORIST PROTECTION OF DIPLOMATIC BUILDINGS BY ARCHITECTURAL PLANNING DECISIONS - Razin, A.D. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Inzhenernye issledovanii͡a, 2017)
The article considers the demands of ensuring the anty-terrorist protection of diplomatic complexes consisting of different types of buildings. As result of analyses systems and means for ensuring the anty-terrorist security is recommended some changes planning squares. It was proposed general planning schemas for considering problems for place systems and means for ensuring the anty-terrorist security diplomatic objects